INFUSION PUMP SURGERY: ACHIEVEMENTS AND LIMITATION (Iraqi Journal of Medical Sciences, 2016)
Background:Infusion pump is a special pump machine, with two different types, programmable and fixed flow pumps. These pumps used for administration of drugs through lumbar intrathecal route.Objectives:To evaluate the infusion pump surgery as a new surgical technique in Iraq used for treatment of pain and spasticity and to discuss the limitations and achievements regarding surgical techniques, the cases that to be selected for surgery and general conditions of selected cases pre and post surgery .Methods: Five patients were collected from Al-Kadhimiya Teaching Hospital complaining of either spastic lower limb due to dorsal spinal tumor, radiculopathy due to bullet injury not relieved by other techniques, or generalized pain due to tumors with different locations and liver metastases. Surgery done for all patients using (Isomed/Medtronic) fixed flow infusion pump.Results:Four patients have pain relief with different percentage when using morphine and one patient with spasticity showed mild improvement after baclofen pump injection.Conclusion:Infusion pump surgery is a new technique in Iraq, which is effective in the management of intractable pain and spasticity not relieved by medications.Keyword: Morphine, baclofen pumps, spasticity, isomed.
Keywords: Morphine; baclofen pumps; spasticity; isomed